2016
DOI: 10.1007/s12253-016-0073-6
|View full text |Cite
|
Sign up to set email alerts
|

Association between IL-6 Gene (−174 & -572 G/C) Polymorphisms and Endometrial Adenocarcinoma Risk

Abstract: We aimed to evaluate the association of IL-6 gene polymorphisms at positions of -174 and -572 and predisposition of endometrial adenocarcinoma (EAC) in a Chinese population. EAC patients have remarkably higher frequency of IL-6 -174 CC genotype [odds ratio (OR) =1.56, 95 % confidence interval (CI) =1.07-2.23; P = 0.03], IL-6 -572 CC genotype (OR =1.93, 95%CI =1.17-3.15; P = 0.01) and IL-6 -174 C allele (OR =1.22, 95 % CI =1.03-1.46; P = 0.04) compared with healthy controls. When stratified with FIGO stage, pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Several studies have demonstrated that SNPs in the -174 promotor region is associated with IL-6 gene transcription, which subsequently influences the expression and secretion of IL-6 (Jerrard-Dunne et al, 2004). For example, a IL-6 SNP in the -572 promoter region is the substitution of cytosine (C) by guanine (G) (Wang et al, 2016). This substitution may influence IL-6 gene transcription and expression level of IL-6, resulting in changes to disease susceptibility (Qi et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated that SNPs in the -174 promotor region is associated with IL-6 gene transcription, which subsequently influences the expression and secretion of IL-6 (Jerrard-Dunne et al, 2004). For example, a IL-6 SNP in the -572 promoter region is the substitution of cytosine (C) by guanine (G) (Wang et al, 2016). This substitution may influence IL-6 gene transcription and expression level of IL-6, resulting in changes to disease susceptibility (Qi et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that the polymorphisms in rs3783553, rs3783550, rs3783546, rs1609682 and rs3783521 of IL-1α ( 138 , 139 ), rs1524107 and rs2066992 of IL-6 ( 140 ), rs4758680 and rs7977932 of IL-31 ( 141 ), rs28372698 and rs12934561 of IL-32 ( 2 ) may be relevant to increased susceptibility to EC in Chinese women. Moreover, the CC genotype of IL-6 Gene (−174 & -572) might contribute to EC risk ( 142 ).…”
Section: Clinical Application Of Interleukins In Ecmentioning
confidence: 99%
“…It has also indicated the proinflammatory milieu can directly increase estrogen production, which may facilitate carcinogenesis by disrupting the estrogen‐progesterone balance (Modugno, Ness, Chen, & Weiss, ). A growing number of studies reported that SNPs locus in interleukin (IL) genes, such as IL‐32 (Yu et al, ), IL‐6 (Wang, Zhang, Zheng, Liu, & Li, ), and IL1A (Yu et al, ), are associated with the risk endometrial cancer. Interleukin 1 receptor type 2 (IL‐1R2) is located on the long arm of human chromosome 2 at band 2q12, belongs to the interleukin 1 receptor family (Boraschi & Tagliabue, ).…”
Section: Introductionmentioning
confidence: 99%